Kesadaran Berpancasila Dalam Mempertahankan Identitas Nasional - Hatta Utwun Billah; Maharani Ariya Yunita; Muhammad Ananda Pratama; Maulia Depriya Kembara (Jurnal Bintang Pendidikan Indonesia, 2023)
The background of this research is to know Pancasila awareness in maintaining national identity. The purpose of this research is to increase awareness of Pancasila in society in the era of globalization. The method used in this research is literature review. From the results of the theoretical study it was found that Pancasila awareness is important in maintaining national identity. In short, Pancasila awareness plays an important role in maintaining national identity. By understanding and practicing Pancasila values, people can strengthen unity, preserve local culture and traditions, strengthen social solidarity and overcome the challenges of globalization. As an effort to maintain national identity.